The structure of spoken language intonation in Romance - Martin, Philippe 1944- (Cambridge University Press, 2015)
"One of the most remarkable features of phonation is the disruption of the normal respiratory cycle. Indeed, outside phonation, the normal cycle of respiration presents a comparable duration for both the inspiration and the expiration (top of Figure 1.1). Figure 1.1 Respiration cycle, without phonation (top) and with phonation (bottom) The first produced prosodic units are breath groups. At early stages of language learning, children mainly use the necessary silent pause in the inspiration phase of their respiratory cycle as boundary markers of these units. The phonation process results from the air flow generated by the lung compression during the respiration-expiration phase. This air flow generates the necessary subglottal pressure needed to produce the vibration of the vocal folds for voiced sounds (vowels, voiced consonants), friction for fricative consonants, and intraoral pressure to allow the production of stop consonants"..
Keywords: Romance languages -- Phonetics -- Intonation; Romance languages -- Phonology; Romance languages -- Phonology, Historical; Romance languages -- Spoken Romance languages; Intonation (Phonetics); Biolinguistics; Romanische Sprachen; Prosodie; Sprachproduktion